CmyView: Walking together apart - Carvalho, Lucila; Freeman, Cristina Garduño (Proceedings of the International Conference on Networked Learning, 2016)
Networked learning practices are impacting the field of cultural heritage, both tangible and intangible, with implications for the way in which places of cultural significance are understood, managed, documented, engaged with and studied. Our research explores the intersection between walking, photography, technology and learning, investigating how mobile devices can be used to foster community participation and assess social value within a networked framework for digital heritage. The paper introduces CmyView, a mobile phone application and social media platform in development, with a design concept grounded on both digital heritage and networked learning perspectives. CmyView encourages people to collect and share their views by making images and audio recordings of personally meaningful sites they see, while walking outdoors. Each person’s walking trajectory (along with their associated images and audio files) then becomes a trace-able artefact, something potentially shareable with a community of fellow walkers. The aim of CmyView is to encourage networked heritage practices and community participation, as people learn to assess their own and experience others social values of the built environment. Drawing on a framework for the analysis and design of productive learning networks, we explore the educational design of CmyView arguing that the platform offers a space for democratic heritage education and interpretation, where participatory urban curatorship practices are nurtured. CmyView reframes social value as dynamic, fluid and located within communities, rather than fixed in a place. The paper presents preliminary findings of the activity of a group of four undergraduate students at an Australian university, who used CmyView to explore the immediate surroundings of their campus. Participants interacted with the platform, mapping, capturing, audio recording their impressions and sites of interest in their walks. In so doing, they created shareable trajectories, which were subsequently experienced by the same group of participants on a second walk. The paper concludes with a discussion about the impact of our research for the design of mobile technologies that embrace participation and sharing, through a networked learning perspective. The paper brings together concepts that sit at the intersection of previously separate fields, namely digital heritage and networked learning, to find their synergies.